1979
DOI: 10.1128/aem.38.6.1052-1055.1979
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopiazonic acid production by Penicillium camemberti Thom and natural occurrence of this mycotoxin in cheese

Abstract: Every Penicillium camemberti strain freshly isolated from 20 commercial cheese brands produced cyclopiazonic acid in two culture media at 25, 13, and 4°C; the toxin yield was greatly dependent on the strain and environmental parameters (medium, temperature, and incubation time). The toxigenic ability appeared as a log-normal distribution. This mycotoxin was found in the crust (0.05 to 0.1 ,ug/g in three samples, 0.1 to 0.2 ,ug/g in five samples, and 0.4, 1, and 1.5 ,Lg/g in three other samples) but not in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(42 citation statements)
references
References 8 publications
3
34
0
5
Order By: Relevance
“…As both metabolites can be detected simultaneously (see Experimental procedures), it is not difficult to include CPA testing when checking for AF. In addition, CPA may be more commonly encountered than AF because of its biosynthesis by both Aspergillus and Penicillium species (Frisvad and Thrane, 2000;Hermansen et al, 1984;Le Bars, 1979;Pitt et al, 1986), and its production over a wide range of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As both metabolites can be detected simultaneously (see Experimental procedures), it is not difficult to include CPA testing when checking for AF. In addition, CPA may be more commonly encountered than AF because of its biosynthesis by both Aspergillus and Penicillium species (Frisvad and Thrane, 2000;Hermansen et al, 1984;Le Bars, 1979;Pitt et al, 1986), and its production over a wide range of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Chemically, it is an indole tetramic acid. The significance of CPA is obscure; however, it is reported to naturally occur in peanuts (Urano and others 1992), corn (Lee and Hagler 1991), and in cheese (LeBars 1979).…”
Section: Types Of Mycotoxinsmentioning
confidence: 99%
“…Sterigmatocystin (STC) was detected and quantified in the surface layer of A. versicolor contaminated hard cheeses at levels ranging from 5 and 600 μg/kg (Northolt and others ). In white cheese, CPA was detected from 0.5 to 1.5 μg/g (Le Bars ) and from 0.02 to 0.08 mg/kg (Zambonin and others ). Stott and Bullerman () showed that when patulin was added to cheddar cheese, it was not detected after storage by TLC.…”
Section: Mycotoxins In Cheesementioning
confidence: 99%
“…Whatever the fungal species (contaminant or fungal ripening cultures), observations have been made, both in vitro and in cheese, that mycotoxin‐producing fungi are inversely correlated with temperature (low or no production at refrigerated temperatures, intermediate production at 12 °C, and optimal production at 20 to 25 °C) (Le Bars ; Wagener and others ; Chang and others ; Sweeney and Dobson ; Finoli and others ; Taniwaki and others ; Bailly and others ; Erdogan and others ). This is not surprising, since low temperature also affects fungal growth that is often, but not systematically, correlated with mycotoxin production.…”
Section: Factors Modulating Mycotoxin Biosynthesis In Cheesementioning
confidence: 99%
See 1 more Smart Citation